Knowledge and Practices of Elementary Teachers on Thematic Approach Towards Inclusive Science Education - Padre, Edna M.; Rostrata, Abby Lyn A.; Anular, Bergin E.; Soriano, Iya G.; Santos, Lovise-Ann O. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study investigated the relationship between the level of knowledge and practice of the thematic approach towards inclusive education among elementary teachers in Iba District, Philippines. A descriptive correlational design was employed, utilizing a survey questionnaire administered to 75 elementary teachers from three selected schools. The findings revealed that the teacher-respondents demonstrated a high level of knowledge and consistently practiced the thematic approach in their teaching strategies, learning activities, instructional materials, and assessment. Furthermore, there is a strong association (r=0.886, p=<0.01) between teachers' knowledge of the thematic approach and their reported use of it in their teaching practices in ensuring inclusive science education. Thus, professional development that enhances teachers' understanding of the thematic approach is recommended, as this is directly associated with improved classroom implementation and more effective inclusive education practices. Additionally, further research could explore the specific impacts of thematic teaching methods on student learning outcomes and inclusivity in diverse classroom settings.